2013
DOI: 10.1590/s0100-736x2013001200014
|View full text |Cite
|
Sign up to set email alerts
|

The normal electrocardiogram in the clinically healthy Saanen goats

Abstract: The purpose of this study was to establish normal reference electrocardiographic (ECG) values for standard limb lead II in Saanen goats. For this, were used 19 healthy adult female Saanen goats. And for reference values for the ECG parameters, were used 95% confidence level. The overall P, Q, R, S and T durations (seconds) were 0.03±0.01, 0.02±0.005, 0.03±0.014, 0.03±0.011, 0.06±0.014 respectively, and the reference values were 0.01-0.04, 0.01-0.02, 0.01-0.06, 0.02-0.04 and 0.04-0.08 respectively. The amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 13 publications
(56 reference statements)
8
19
3
1
Order By: Relevance
“…The results of the present study showed that the value of ST-segment duration ranged from 0.08±0.01 to 0.22±0.02 (second) with an average of 0.11±0.01 and 0.16±0.01 in sheep and goats, respectively. Our findings showed that ST-segment duration in goats was little different from that reported by Pogliani et al (2013) in Saanen goats (0.15±0.041) and was less than what was reported by Ahmed and Sanyal (2008) in Black Bengal goats (0.19±0.014). Also our findings showed that ST-segment duration in Kermani sheep was less than that reported by Ahmed and Sanyal (2008) in Garol sheep (0.13±0.010).…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…The results of the present study showed that the value of ST-segment duration ranged from 0.08±0.01 to 0.22±0.02 (second) with an average of 0.11±0.01 and 0.16±0.01 in sheep and goats, respectively. Our findings showed that ST-segment duration in goats was little different from that reported by Pogliani et al (2013) in Saanen goats (0.15±0.041) and was less than what was reported by Ahmed and Sanyal (2008) in Black Bengal goats (0.19±0.014). Also our findings showed that ST-segment duration in Kermani sheep was less than that reported by Ahmed and Sanyal (2008) in Garol sheep (0.13±0.010).…”
Section: Discussioncontrasting
confidence: 83%
“…Although, the heart rate of goats is higher than sheep (Radostits et al, 2007; and there is a negative correlation between ST-segment duration and heart rate, (Jafari-Dehkordi et al, 2012;Milhorn, 2005;Pogliani et al, 2013) in the current study, the ST-segment duration in goats was longer than in sheep. Inter species difference, the conductive properties of the body mass and the volume of the gastrointestinal tract can influence the distribution of electrical potentials to the body surface (Santamarina et al, 2001) and this may explain the different ST-segment duration between the sheep and goats in our study.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations